Description of an anomalous tortoise (Reptilia: Testudinidae) from the Early Holocene of Zimbabwe - Broadley, Donald G. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2007)
An anomalous subfossil tortoise is described from a Holocene cave deposit at Pomongwe in the Matobo Hills, southwest Zimbabwe (Carbon 14 date 9400 ±100 yrs BP). This specimen appears to be unique in its truncated and depressed anterior carapace with loss of the normal second peripheral, but agrees with Kinixys Bell and Impregnochelys Meylan & Auffenberg in having numerous auxiliary scales. It may lack the carapacial hinge of Kinixys. The epiplastron appears most similar to that of a female Chersina angulata Gray.